(untitled) (REMUNOM, 2024)
Fish waste, when disposed of irregularly, entails several environmental, social and economic risks. On the other hand, when well used, it can be used in the production of animal feed, biogas, biofertilizers and organic compounds. In this study, based on the literature, the main environmental, economic and productive benefits of using fish waste in agriculture through fertilization were described. To this end, an integrative review of data published between 2012 and 2022 was carried out. The selection of papers followed inclusion and exclusion criteria through dynamic reading and, in the end, 12 studies were selected, published in Portuguese. and English, whose theme addressed the use of fish waste in agriculture through the composting process or as biofertilizers. The integrative analysis of the studies showed that the use of fish waste to make organic fertilizers is an economically viable, environmentally favorable and productively expressive alternative. Productivity results showed that some crops can produce up to 60% more in soils fertilized with residue, generating greater economic returns for producers. The use of organic compounds derived from the use of fish waste reduces the environmental impacts caused by the irregular disposal of this product and also adds value to products grown through ecological production, free of synthetic fertilizers and pesticides. It was also seen that organic compounds and biofertilizers can have multiple uses, either on the property, increasing soil fertility and crop productivity or as an economic product, being sold at fairs, hortifrutis and even in agricultural product stores, generating extra income to producers.